Aeromonas hydrophila-related fulminant necrotizing fasciitis and arterial embolization after plaster placement in Gustilo I distal radius fracture: a case report and literature review - Zhen Zhang; Xiao-Dan Zhao; Guanglin Wang; Fuguo Huang (BMC Musculoskeletal Disorders)
Abstract Background Distal radius fractures are prevalent among the elderly. In cases of Gustilo I open distal radius fractures, standard initial management involves irrigation, debridement, reduction, and external fixation. Subsequently, external fixation may serve as the definitive treatment or transition to internal fixation. However, rare instances of fulminant necrotizing fasciitis and arterial embolization induced by Aeromonas hydrophila infection have been reported during the initial external fixation. Case presentation A 72-year-old healthy female with a Gustilo I open distal radius fracture underwent irrigation, debridement, reduction, and plaster placement. The patient experienced heightened pain, sensory loss, and arm swelling 8 hours later, and was then diagnosed with septic shock with Aeromonas hydrophila infection, necrotizing fasciitis, and arterial embolization 20 hours later. The patient received antibiotic administration and life-saving amputation. A vancomycin/gentamycin bone cement spacer was introduced into the void resulting from extensive debridement during the surgery. Postoperatively, the patient developed multiple organ dysfunction syndrome (MODS), which resolved within 5 days. Wound closure was subsequently performed in a second surgery, leading to a successful and robust recovery. Conclusions In managing open fractures among the elderly exposed to natural water sources, careful consideration is crucial due to the potential risk of anaerobic bacterial infection and necrotizing fasciitis associated with plaster or splint placement, creating a hypoxic environment.